Compared to the optimism and emotional relationship of balance for students of Physical Education - Saeed, Amer; Ali, Amal; Sabah, Hydar (Journal of Physical Education, 2014)
The research aims to identify the optimism and emotional balance among the students of the various stages in the Faculty of Physical Education of the University of Babylon, and the differences in optimism and emotional balance between students of different stages in the Faculty of Physical Education of the University of Babylon , as well as the relationship between optimism and emotional balance them. Researchers have identifie the research community to ( 579 ) students, chose them ( 120 ) students stratified random manner, and by (30 ) students for each phase. It was the use of the descriptive methods of survey and comparative studies and relations correlation to the suitability of the nature of the search, and then they began to apply the standard of optimism and emotional balance on the sample and after treatments required statistical results appeared was most notably marked by the students of the Faculty of Physical Education at the University of Babylon various stages varying optimism good grades amid the emotional balance, and there are real differences between the students of first and second phases of the Faculty of Physical Education in optimism , as well as the existence of a correlation between optimism and emotional balance for each of the students of Physical Education at the University of Babylon.